Treatment strategy for pediatric giant mucinous cystadenoma: A case report - Shun Watanabe; Shunsuke Nagashima; Chihiro Onagi; Nobuto Yamazaki; Shuhei Shimada; Masato Sakai; Shun Yanai; Yoichi Haga; Akira Ohara; Minoru Kuroiwa (MDPI AG, 2019)
Because of their rarity, the treatment strategy for pediatric ovarian epithelial tumors is controversial, especially for a giant cystadenoma. We report the largest mucinous cystadenoma (MCA) case in the pediatric literature thus far. A 12-year-old girl had abdominal distention and visited our hospital. She had a multilocular cyst with some protuberance on the inside and high values of CA 19-9 and CA-125. We diagnosed her with a left MCA and performed a left oophorectomy. The tumor was the stage IA borderline malignant MCA and weighed 11.8 kg. Five years have passed, the patient has not experienced recurrence or metastasis. The resection of giant tumors can affect respiration and circulation. However, pre- or intra-operative drainage may lead to dissemination and adhesion. When we treat pediatric giant ovarian epithelial tumors, we must understand the findings that suggest the possibility of malignancy to decide appropriately as to whether drainage should be performed.